Memory Prosthesis: Is It Time for a Deep Neuromimetic Computing Approach? - Cutsuridis, Vassilis (Frontiers in Neuroscience, 2019)
Memory loss, one of the most dreaded afflictions of the human condition, presents considerable burden on the world’s health care system and it is recognized as a major challenge in the elderly. There are only a few neuro-modulation treatments for memory dysfunctions. Open loop deep brain stimulation is such a treatment for memory improvement, but with limited success and conflicting results. In recent years closed-loop neuropros-thesis systems able to simultaneously record signals during behavioural tasks and generate with the use of inter-nal neural factors the precise timing of stimulation patterns are presented as attractive alternatives and show promise in memory enhancement and restoration. A few such strides have already been made in both animals and humans, but with limited insights into their mechanisms of action. Here, I discuss why a deep neuromimetic computing approach linking multiple levels of description, mimicking the dynamics of brain circuits, interfaced with recording and stimulating electrodes could enhance the performance of current memory prosthesis systems, shed light into the neurobiology of learning and memory and accelerate the progress of memory prosthesis research. I propose what the necessary components (nodes, structure, connectivity, learning rules, and physi-ological responses) of such a deep neuromimetic model should be and what type of data are required to train/ test its performance, so it can be used as a true substitute of damaged brain areas capable of restoring/enhancing their missing memory formation capabilities. Considerations to neural circuit targeting, tissue interfacing, elec-trode placement/implantation and multi-network interactions in complex cognition are also provided.